Dynamics Of Food Commodity Prices And Local Inflation Post-Earthquake: A Literature Review Of The Model Economic Disaster Prediction - Alhusna Nupiah; Dini Sisri Putri; M. Hasbi Nasution (Citakonsultindo, 2026)
Earthquake earth is shock exogenous that fundamentally disrupts​ chain supply food and trigger volatility price commodities strategic at the level local, but the prediction model conventional often fail​ catch magnitude impact current consequence complexity mechanism non - linear transmission. Research This aim For synthesize corpus literature about dynamics price food and inflation local post-earthquake as well as evaluate evolution of predictive models economy disaster. The method used is studies literature with data sources in the form of books, articles journal scientific, and reports research. Synthesis results disclose four findings main. First, disruption chain supply and panic buying behavior creates scarcity the pseudo that pushes volatility price extremes in commodities rice, chilies, and cooking oil. Second, transmission impact show differentiation spatial significant, with the island region experience pass-through and persistence coefficients inflation more tall compared to land areas. Third, there is shift paradigm modeling from approach balance such as Input-Output and CGE towards approach complexity such as Agent-Based Modeling and Big Data analysis. Fourth, effectiveness market intervention is of a nature contextual, with essential market operations in the phase I temporary cash transfer without condition more effective in the phase recovery. Research conclusions confirm the need approach hybrid in modeling and policy stabilization differentiated pricing​ in a way spatial as well as sequenced temporally. Implementation results research directed at development system warning early inflation big data based, strengthening logistics contingency in the archipelago region, and the formation of group task integrated For stabilization price post-disaster.